Das schwarze Wien Bautätigkeit im Ständestaat 1934-1938 - Suttner, Andreas (2017)
This book deals with the housing- and settlement-policy of the authoritarian Austrian Corporate State (Staendestaat) in Vienna between 1934 and 1938. National and international dialogues led to building strategies for a car-friendly city. Different types of flats, settlements and administration buildings will be shown, as well as planned monumental buildings of the unity party Fatherland Front (Vaterlaendische Front).